Design and Fabrication of the Large Thrust Force Piezoelectric Actuator - Shyang-Jye Chang; Jing Chen (Advances in Materials Science and Engineering)
This paper presents a novel piezoelectric actuator containing double pushers. By using finite element analysis software, this study simulated the vibration mode and amplitude of piezoelectric actuators. The Taguchi method was used to design the parameters of piezoelectric actuators including length, width, height, and electrodes setting. This paper also presents a discussion regarding the influence that the design parameters had on the actuator amplitudes. Based on optimal design parameters, a novel piezoelectric actuator containing double pushers is produced and some thrust tests are also carried out. From the experiment results, the piezoelectric actuator containing double pushers can provide a greater thrust force than that of traditional actuators containing a single pusher as the preload is greater. Comparing with the traditional actuators, the thrust force of new actuator can be increased by 48% with the double preload.